2019
DOI: 10.1590/0037-8682-0266-2019
|View full text |Cite
|
Sign up to set email alerts
|

A major chikungunya epidemic with high mortality in northeastern Brazil

Abstract: Introduction: Chikungunya causes fever and severe and persistent joint pain. Methods: We reported a chikungunya outbreak that occurred in Ceará State, Brazil between 2016 and 2017 with emphasis on epidemiological characterization of cases, high number of deaths, mortality-associated factors, and spatial and temporal spread of the epidemic among municipalities. Results: In November 2015, the first autochthonous cases of chikungunya were confirmed in Ceará, Brazil. In 2016-2017, 195,993 cases were reported, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 11 publications
0
25
0
5
Order By: Relevance
“…Studies have shown that the presence of comorbidities, such as diabetes, hypertension, and kidney disease, were significantly associated with death from CHIK 10,39,45 , and the number of comorbidities increased with age, which may explain the high number of deaths among individuals aged over 65 years in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Studies have shown that the presence of comorbidities, such as diabetes, hypertension, and kidney disease, were significantly associated with death from CHIK 10,39,45 , and the number of comorbidities increased with age, which may explain the high number of deaths among individuals aged over 65 years in this study.…”
Section: Discussionmentioning
confidence: 60%
“…However, it was possible to identify spatial clusters for dengue presence and a spatial dispersion of chikungunya and Zika. The occurrence of outbreaks of chikungunya and Zika in both study sites could explain the widespread presence of cases in each city [17, 29, 32, 45–47]. However, the magnitude of chikungunya’s outbreak in Fortaleza was larger compared with the outbreak of Zika in the same city [45, 47] and to chikungunya and Zika in Medellin.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of outbreaks of chikungunya and Zika in both study sites could explain the widespread presence of cases in each city [17, 29, 32, 45–47]. However, the magnitude of chikungunya’s outbreak in Fortaleza was larger compared with the outbreak of Zika in the same city [45, 47] and to chikungunya and Zika in Medellin. Although both sites are known for the presence of arboviruses, differences in disease distribution could be attributed to environmental differences including altitude and temperature or other socio‐environmental factors associated to vector presence and population’s immunological profile in each site [1, 2, 17, 44, 45, 47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, the Zika virus (ZIKV) started to circulate in the Northeast region of Brazil and, in the following years, caused an epidemic with more than 200,000 reported cases. This virus has been associated with many neurological disorders, including congenital syndrome caused by the Zika virus and Guillain-Barré syndrome [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%